The Effect of Practice on The Level of Some Elements of Physical Fitness of The Young Female Soccer Players In the Palestinian Clubs - Abutame, Bahjat Ahmad; Lahlooh, Sama Walid; Baaziz, Mohamed; Abderrahman, Abderraouf Ben (Advances in Social Sciences Research Journal, 2024)
The study aimed to identify the level of some elements of physical fitness among female soccer players in Palestinian clubs, in addition to identifying differences in the level of fitness according to the variable years of playing: (1-2 years, 3 years or more). To achieve this, the researchers used the descriptive approach, using and conducting physical tests (speed, flexibility, endurance, agility, and muscular strength) on a stratified random sample of (89) emerging female soccer players. The results of the study showed that the level of physical fitness among young female soccer players in Palestinian clubs was good, as a function of the arithmetic average of the physical fitness elements, respectively: speed (8.9) m/s, flexibility (6.05) cm, endurance (2.39) m/min, Agility (14.7) m/s, muscular ability (1.45) meters. The results of the study showed that there are no differences in the level of some elements of physical fitness among female soccer players due to the variable years of playing. The researchers recommended the need for continuous training to improve and develop the level of physical fitness among female soccer players in Palestinian clubs.